Interplanetary shock transmitted into the Earth's magnetosheath: Cluster and Double Star observations - G. Pallocchia; A. A. Samsonov; M. B. Bavassano Cattaneo; M. F. Marcucci; H. Rème; C. M. Carr; J. B. Cao (Annales Geophysicae, 2010)
On day 7 May 2005, the plasma instruments on board Double Star TC1 and Cluster SC3 spacecraft register inside the magnetosheath, at 19:15:12 and 19:16:20 UT, respectively, a strong pressure pulse due to the impact of an interplanetary shock wave (IS) on the terrestrial bow shock. The analysis of this event provides clear and quantitative evidences confirming and strengthening some results given by past simulations and observational studies. In fact, here we show that the transmitted shock is slowed down with respect to the incident IS (in the Earth's reference frame) and that, besides the transmitted shock, the IS – bow shock interaction generates a second discontinuity. Moreover, supported also by a special set three-dimensional magnetohydrodynamic simulation, we discuss, as further effects of the interaction of the IS with the magnetosphere, other two interesting aspects of the present event, that is: the TC1 double crossing of the bow shock (observed few minutes after the impact of the IS) and the presence, only in the SC3 data, of a third discontinuity produced inside the magnetosheath.